Variation in leaf morphological, stomatal, and anatomical traits and their relationships in temperate and subtropical forests - Congcong Liu (Nature Portfolio, 2019)
Abstract Leaf functional traits have attracted the attention of ecologists for several decades, but few studies have systematically assessed leaf morphological traits (termed “economic traits”), stomatal (termed “hydraulic”), and anatomical traits of entire forest communities, thus it is unclear whether their relationships are consistent among trees, shrubs, and herbs, and which anatomical traits should be assigned to economical or hydraulic traits. In this study, we collected leaf samples of 106 plant species in temperate forests and 164 plant species in subtropical forests and determined nine key functional traits. We found that functional traits differed between temperate and subtropical forests. Leaf traits also differed between different plant functional groups, irrespective of forest type; dry matter content, stomatal density, and cell tense ratio followed the order trees > shrubs > herbs, whereas specific leaf area and sponginess ratio showed the opposite pattern. The correlations of leaf traits were not consistent among trees, shrubs, and herbs, which may reflect different adaptive strategies. Principal component analysis indicated that leaf economics and hydraulic traits were uncoupled in temperate and subtropical forests, and correlations of anatomical traits and economic and hydraulic traits were weak, indicating anatomical traits should be emphasized in future studies.